Preventing atrial fibrillation by combined right isthmus ablation and cryoballoon pulmonary vein isolation in patients with typical atrial flutter: PAF‐CRIOBLAF study. Issue 5 (28th August 2021) - Anselme, Frédéric; Savouré, Arnaud; Clémenty, Nicolas; Cesari, Olivier; Pavin, Dominique; Jesel, Laurence; Defaye, Pascal; Boveda, Serge; Rivat, Philippe; Mansourati, Jacques; Mechulan, Alexis; Cebron, Jean‐Pierre; et al.
Abstract: Background: Although less common, typical atrial flutter shares similar pathophysiological roots with atrial fibrillation. Following successful cavo‐tricuspid isthmus ablation using radiofrequency, many patients, however, develop atrial fibrillation in the mid‐to‐long‐term. This study sought to assess whether pulmonary vein isolation conducted at the same time as cavo‐tricuspid isthmus ablation would significantly modify the atrial fibrillation burden upon follow‐up in patients suffering from typical atrial flutter. Methods: This was a multicenter randomized controlled study involving typical atrial flutter patients with history of non‐predominant atrial fibrillation (1 atrial fibrillation episode only, in 67% of population) who were scheduled for cavo‐tricuspid isthmus radiofrequency ablation. Patients were randomly assigned to either undergo cavo‐tricuspid isthmus ablation alone or cavo‐tricuspid isthmus plus pulmonary vein isolation (CTI+). Pulmonary vein isolation was performed using cryoballoon technology. An outpatient consultation with ECG and 1‐week Holter monitoring was performed at 3, 6 months, 1 year, and 2 years postprocedure. The primary endpoint was atrial fibrillation recurrences lasting more than 30 s at 2 years postablation. Results: Of the patients enrolled, 36 were included in each group. At 2‐year follow‐up, the atrial fibrillation recurrence rate was significantly higher in the CTI vs CTI+group (25/36, 69% vs. 12/36, 33% respectively; P  < .001), with similar typical atrial flutter recurrence rates. There were no differences in undesirable events, except for transient phrenic nerve palsy reported from three CTI+patients (8.3%). Conclusion: Pulmonary vein isolation using cryoballoon technology was proven to significantly reduce the atrial fibrillation incidence at 2 years postcavo‐tricuspid isthmus ablation. Abstract : Atrial flutter (AFl) patients with prior occasionally recorded atrial fibrillation (AF) were randomly assigned to undergo cavo‐tricuspid isthmus (CTI) ablation or CTI plus pulmonary vein isolation (combined atrial flutter ablation). AF was neither the predominant (67% of the population with only one recorded AF episode) nor the targeted arrhythmia. At 2‐year FU, AF recurrences were significantly higher in atrial flutter ablation group vs combined atrial flutter group with similar AFL recurrences.